The effect of Ukrainian refugees on the local labour markets: the case of Czechia - Agnieszka Postepska; Anastasiia Voloshyna (Journal of Population Economics, 2025)
Following the Russian Federation's invasion of Ukraine on 24thFebruary 2022, over a quarter of the Ukrainian population became displaced. Czechia emerged as a key destination, granting temporary protection to approximately 433,000 Ukrainians by the end of 2022, thus sheltering the highest per capita number of Ukrainian refugees worldwide. The swift enactment of the `Lex Ukraine Act' granted the refugees unrestricted access to the labour market. This led to a notable increase in the number of legally employed Ukrainians and expanded Czechia's workforce. Using individual micro-level data from 16 waves of the Labour Force Sample Survey (LFSS), collected between the 1stquarter of 2019 and the 4thquarter of 2022, we examine the short-term impact of the influx of the Ukrainian refugees into the workforce on the labour market outcomes of locals in Czechia. Incorporating several empirical strategies, including a two-way fixed effects model (TWFE), extensions to the canonical difference-in-differences (DiD) estimator, and matching on selective characteristics of individuals/districts and pre-treatment trends, we find consistent evidence that the influx of refugees had no economically meaningful impact on employment, unemployment, or inactivity rates within the local population, regardless of gender, educational level, or industry. Most importantly, we find consistent evidence of an increase in weekly working hours among local females in treated districts. This increase is primarily driven by workers with secondary education employed in the most affected sectors.
Keywords: F22; J15; J21; 330; Ukrainian refugees; Immigrants; Local labour market; Labour supply